THE APPLICATION OF CHAMOMILE TEA AND HONEY COMBINATION TO REDUCE INSOMNIA IN PERIMENOPAUSE WOMEN - Situmorang, Melisha; Qomar, Umi Laelatul; Dewi, Adinda Putri Sari (Prosiding University Research Colloquium, 2024)
According to WHO, in 2025 the number of postmenopausal women in Asia will increase from 107 million to 373 million. Perimenopause is the stage of a woman's last menstrual period between the ages of 45-55 years, with complaints such as anxiety, sleep disturbances, and difficulty sleeping which is called insomnia. Sleep disorders if not resolved will increase anxiety to depression and suicide. The incidence of insomnia in perimenopause is quite high, namely 67% in 2014. Insomnia in several studies can be overcome by Chamomile tea containing an antioxidant called apigenin to provide calm and increase the hormone serotonin so that the sleep quality becomes better. This research used a case study. The research subjects were 4 female respondents who experienced insomnia in perimenopause aged 46-51 years according to the inclusion and exclusion criteria. The data in this study used the PSQI questionnaire. The intervention was carried out for 14 days from the time the respondent filled out the PSQI, the respondent was given 14 Chamomile tea sachets and 1 pot of honey to drink once a day for 14 days. After giving the combination of Chamomile Tea and Honey for 14 days, all respondents experienced a decrease in anxiety so that the sleep quality of the respondents based on the results of the PSQI test experienced a 100% increase in sleep quality. The combination of Chamomile and Honey tea can improve sleep quality in perimenopausal women.